First record of Feltiella curtistylus Gagné (Diptera: Cecidomyiidae) in Argentina = Primer registro de Feltiella curtistylus Gagné (Diptera: Cecidomyiidae) en Argentina - Funes, Claudia Fernanda; Escobar, Lorena Ines; Palavecino, Braian Eduardo; Kirschbaum, Daniel Santiago (Facultad de Ciencias Agrarias, Universidad Nacional de Cuyo, 2020)
The first records of Feltiella curtistylus Gagné (Diptera: Cecidomyiidae) in Argentina are reported. Larvae from this species were captured in strawberry (Fragaria x ananassa Duch.) leaflets heavily infested with Tetranychus urticae Koch (Acari: Tetranichidae) in Famaillá, province of Tucumán, Argentina (27°03’S, 65°25’W). In 2015 (June, September and October), 16 larvae were collected; in 2016 (October, November and December), 23 larvae; and in 2017 (September, October and November), 49 larvae. Since F. curtistylus was found associated to a mite of agricultural importance in strawberry crops, this predatory gall midge has a potential for being considered a biological control agent.